Implementasi Pendidikan Berkarakter yang Berorientasi Nilai – Nilai Moral - Yang Gusti Feriyanti; Trisna Rukhmana; Rona Romadhianti; Athiyah Salwa; Durrotun Nafisah; Gamar Al Haddar (Departement of Mathematics Education, 2024)
This journal discusses the implementation of character education oriented towards moral values ​​as an integral strategy in shaping the character of students. Involving an analysis of the concept of character education and moral values, this research explores the methods, strategies and impacts of this implementation. The research results show that this approach makes a positive contribution to character development, increases moral awareness, and produces students who are more ethically resilient. Despite facing a number of challenges, such as limited resources and resistance to change, this journal presents recommendations to increase the effectiveness of implementation, including improving the curriculum and teacher training. In conclusion, the implementation of character education oriented towards moral values ​​has great potential in forming individuals who are committed to moral integrity.